El escarabajo de oro y las posibilidades del ars combinatoria. - Copertari, Gabriela (Studies in Latin American Popular Culture, 2025)
This article focuses on The Golden Bug—Or Victorias Hämnd (2014), codirected by the Argentine filmmaker Alejo Moguillansky and the Swedish artist Fia-Stina Sandlund. Although the film is a product of the collaboration between both directors, the imprint of Moguillansky's poetics is evident, which has as one of its foundations ars combinatoria and, in that sense, has a strong Borgesian influence. The political meanings produced in the film by three different possibilities of ars combinatoria are analyzed. First, the combination of different arts is analyzed to demonstrate that this sometimes becomes a formal anchor of the conflict between Latin America/men/anticolonialism and Europe/women/feminism, as each art represents a particular geocultural reference, Europe or Latin America, producing a constant cultural decentering and thus questioning essentialism in national and cultural identities. Second, the article analyzes the way the film combines and parodies identity discourses and politics, such as nationalism and essentialist feminism. Finally, it is proposed that, through theft—which gives fictional form to the anticolonialist discourse that constitutes the ideological skeleton of the film—and the combination and proliferation of stories that it triggers, the film traces a continuity between the colonialism of the past and the colonialism of the present.